Evaluation of efficacy of ultrasound‐guided microwave ablation in primary hyperparathyroidism. Issue 2 (5th January 2022) - Zhang, Mingzhu; Gao, Yuxiu; Zhang, Xiaojuan; Ding, Zhaoyan; Wang, Xinya; Jiang, Wenbin; Zhao, Cheng
Abstract: Purpose: We aimed to evaluate the clinical efficacy and safety of ultrasonographically (US)‐guided percutaneous microwave ablation (MWA) in the treatment of primary hyperparathyroidism (PHPT). Methods: A total of 35 patients who received MWA treatment in our hospital between August, 2019 and January, 2021 were retrospectively analyzed. Serum parathyroid hormone (PTH), calcium, phosphorus levels, and improvement in clinical symptoms were recorded before and after MWA. All patients were followed up for 6 months. Paired‐sample t ‐tests and paired sample Wilcoxon signed‐rank tests were used to indicate PTH, calcium, and P levels before and after ablation. Postoperative complications were statistically analyzed to evaluate the therapeutic effect of MWA on PHPT patients. Results: A total of 38 parathyroid nodules in 35 PHPT patients were completely ablated at one time. These results indicated that MWA could effectively destroy parathyroid tissue and decrease the concentrations of PTH, calcium, and phosphorus compared with those before MWA, and the effect was sustained. Moreover, MWA improved clinical symptoms, and improved quality of life of patients. None of patients developed tracheal and esophageal injuries, peripheral hematoma, infection, or other serious complications. Conclusion: US‐guided MWA has shown to be an effective and safe approach to treat PHPT patients. Abstract : The ablation procedures of the patient